Stability and bioaccessibility of iron in pumpkin discs vacuum impregnated with ferrous gluconate, β-cyclodextrin and ascorbic acid - Lencina, María Sabrina (2022)
Present work evaluates the content and bioaccessibility of iron in vacuum-cooked pumpkin discs (VCPD) impregnated with ferrous gluconate (FeGlu) solutions added with β-cyclodextrin (BCD) and/or ascorbic acid (AA). The stability of Fe2+, AA and color of the VCPD after refrigerated storage were also studied. Pumpkin discs treated with any of the FeGlu studied solutions reached a total iron content between 17 and 20 mg Fe2+/100 g. Addition of BCD or AA to FeGlu solution improved Fe2+ of VCPD compared to control fortified only with FeGlu. After in vitro digestion, soluble Fe2+ was also significantly higher in pumpkins impregnated with BCD and AA solutions. Both BCD and AA probably exert their positive effect favoring the solubility of iron and/or the stability of the ferrous iron form, being the bioaccessibility of Fe2+ approximately 17 and 20% w/w respectively, and 10% for the FeGlu-impregnated discs. Although BCD did not have the impact observed for AA, a synergistic effect was observed in BCD-FeGlu-AA systems, where the proportion of Fe2+ was approximately 50% higher than in FeGlu after 21 days of refrigerated storage. The use of BCD and AA also allowed to better maintain the color of the fortified pumpkin discs after cooking and refrigerated storage.